Tanggung Jawab Hukum Bidan dalam Telekonsultasi Kebidanan dalam Perspektif Peraturan Per-Undang-Undangan dan Etika Profesi - Inna Noor Inayati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The development of digital technology in health services has encouraged the birth of new forms of services in the form of teleconsultation, including in midwifery practice. On the other hand, legal and ethical challenges have emerged to the implementation of these services by midwives, given the limitations of normative regulations that explicitly accommodate teleconsultation practices. This study aims to examine the legal responsibilities of midwives in the practice of midwifery teleconsultation, reviewed from the perspective of laws and regulations, namely Law No. 17 of 2023 concerning Health, Minister of Health Regulation No. 28 of 2017 concerning Licensing and Implementation of Midwife Practice, Minister of Health Regulation No. 24 of 2022 concerning Medical Records, Minister of Health Regulation No. 20 of 2019 concerning the Implementation of Telemedicine between Health Service Facilities, and the Midwifery Professional Code of Ethics. The method used in this study is normative juridical with a statutory approach and professional ethics. The results of the discussion show that legally, the practice of teleconsultation in general has been regulated in Law No. 17 of 2023, but specifically for the midwife profession it is still in a gray area because it has not been explicitly accommodated in Permenkes No. 28 of 2017, and is explicitly limited in Permenkes No. 20 of 2019 only for between health service facilities. On the other hand, legal responsibility remains with midwives for actions taken online, including the obligation to document through electronic medical records (Permenkes No. 24 of 2022), the principle of informed consent, and protection of patient data. From an ethical perspective, midwives are required to uphold the principles of professionalism, nonmaleficence, and protection of patient rights. In conclusion, a policy reformulation is needed that explicitly regulates the limits and procedures for teleconsultation by midwives to ensure legal certainty and ethics of digital-based midwifery services.